Cancer mortality in the Mexican Social Security Institute, 1989-2013 - Víctor Hugo Borja-Aburto; Javier Dávila-Torres; Ramón Alberto Rascón-Pacheco; Margot González-León; José Esteban Fernández-Gárate; Ivonne Mejía-Rodríguez; José de Jesús González-Izquierdo; Pedro Mario Escudero-de los Ríos (Instituto Nacional de Salud Pública, 2016)
Objective. To analyze cancer mortality in affiliates of the Mexican Social Security Institute (Instituto Mexicano del Seguro Social -IMSS) and time trends in the risk of death due to cancer from 1989 to 2013.  Materials and methods. A descriptive analysis of cancer mortality trends in beneficiaries of the IMSS was performed. Age and sex adjusted mortality rates were obtained using direct standardization with the WHO population. Changes in the risk of death due to  cancer over time were evaluated using Poisson regression. Results. The absolute number of deaths due to cancer doubled from 1989 to 2013 due to increasing age of the affiliate population. The risk of death among affiliates decreased for the majority of cancers except for colon and rectal cancer. Conclusion. The risk of dying from cancer among IMSS affiliates showed a marked decrease, which may be due to an increase in detection and opportune treatment.  DOI: http://dx.doi.org/10.21149/spm.v58i2.7784